The Multi-Level Governance Dilemma in Mandalika Special Economic Zone: A Bargaining and Cooperation Approach - Roseno Aji Affandi; Salsa Nabila Putri; Tirta Nugraha Mursitama; Yanyan Mochamad Yani; Arry Bainus (Jurnal Hubungan Internasional, 2024)
This study’s background is based on the social and political tension in developing the SEZ in Indonesia. The research concluded that the main problems in SEZ development stemmed from three main factors: (1) lack of comprehension of multi-level governance, both from the central and local governments; (2) too-centralized government imposing top-down regulation; (3) lack of skills from the local government and local community to negotiate and collaborate with the multi-stakeholders. This study disclosed that Mandalika SEZ has encountered the same problem, specifically the lack of the role of local government and local communities in participating in Mandalaika SEZ sports tourism development. This study is crucial in terms of its contribution to theory and fieldwork investigation. This study investigated the political economy impacts of Mandalika SEZ by employing the integration of Multi-Level Governance (MLG) and Bargaining and Cooperation (BNC) theories. The integration of these theories is novel and differentiates them from previous research. This study employed a qualitative research approach, utilizing stakeholder interviews as the primary data source, complemented by secondary data obtained from prior research.